Practicality of hierarchically macro/mesoporous γ-Al2O3 as a promising sorbent in the preparation of low specific activity 99Mo/99mTc generator. (December 2021) - Wang, Jieru; Gao, Ruiqin; Huang, Qinggang; Yin, Xiaojie; Lin, Mu; Cao, Shiwei; Chen, Desheng; Fan, Fangli; Wu, Xiaolei; Qin, Zhi; Guo, Zhijun; Bai, Jing; et al.
Abstract: Hierarchically macro-/mesoporous γ-Al2 O3 (HMMA) was synthesized and characterized by various analytical techniques. The results indicated that HMMA possessed macropores (∼0.45 μm) and mesopores (∼10.6 nm) with a large surface area (∼542 m 2 g −1 ). The absorption behaviors of Mo and Re with HMMA were investigated. The maximum static absorption capacity could reach about 250 mg Mo per g HMMA. The absorption equilibrium can be attained quickly within 10 mins. At initial Mo ions concertation of 10, 000 mg L −1, the breakthrough capacity was determined to be around 200 mg Mo per g HMMA. Additional, absorption mechanism results indicated that Mo ions reacts strongly with a hydroxyl on the surface of γ-Al2 O3 and an adjacent Al atom, simultaneously. A 9.15 mCi (339 MBq) 99 Mo generator was prepared and evaluated its performance for over one week. The recovery of 99m Tc could reach about 89% with favorable radionuclidic, radiochemical and chemical purity for nuclear medicine application. HMMA has a potential application prospect for the preparation of low specific activity (LSA) 99 Mo/ 99m Tc generator. Highlights: HMMA showed high absorption capacity to Mo ions. LSA 99 Mo/ 99m Tc generator used HMMA as column materials has been prepared. 99m Tc eluted from 99 Mo/ 99m Tc generator were used for preparation of radiopharmaceuticals using MDP and MIBI.